PENGELOLAAN KAWASAN HUTAN ADAT PADA MASYARAKAT ADAT DAYAK IBAN DUSUN SUNGAI UTIK KABUPATEN KAPUAS HULU - NIM. A1011201250, BERNICA VAN BERTI (Jurnal Fatwa Hukum, 2024)
Abstract  The customary forest area for the Dayak Iban community is not just a source of life, but rather a place that accommodates spiritual values to preserve traditions that become cultural identity, rights and local knowledge that will be passed on to future generations. Even though this has been acknowledged, the protection and rights of indigenous peoples are still not optimally accepted by the Dayak Iban Indigenous People of Sungai Utik. The Sungai Utik Customary Forest is still being disturbed by the authorities. This kind of conflict often involves misalignment between the perspectives of indigenous peoples, the government, and other parties who have an interest in natural resource management, especially in the Sungai Utik traditional forest area.The research method used in this research is an empirical research method with a descriptive analysis approach, namely using information, data and facts in the field which will be used to analyze research problems. This research was conducted through direct communication techniques. The formulation of the research problem is: How is the Management of Customary Forest Areas in the Dayak Iban Community of Sungai Utik Kapuas Hulu After the Issuance of the Decree Determining the Dayak Iban Customary Forest at Sungai Utik. The research objectives of this research are to obtain data and information on the management of customary forest areas before and after the issuance of the decree on determining customary forests, the obstacles and implications of the issuance of the Decree) on determining customary forests on the level of conflict and community efforts to prevent tenure conflicts.Based on the research results, it can be revealed that the management of the Dayak Iban community's customary forest area experienced positive changes after the issuance of the Decree establishing customary forests in Sungai Utik. There is an increase in awareness of the importance of preserving customary forests, along with the implementation of more structured and measurable policies and of course a reduction in tenure conflicts that occur in the customary forest area of Sungai Utik. Although there are still obstacles, the implications of the issuance of the Decree on Determining the Sungai Utik Customary Forest have decreased. level of conflict  Keywords: Customary Forest, Forest Management.    Abstrak  Kawasan hutan adat bagi masyarakat Dayak Iban bukan hanya sebatas sumber kehidupan semata, melainkan sebagai salah satu wadah yang menampung nilai spritual untuk melestarikan tradisi yang menjadi identitas budaya, hak-hak dan pengetahuan lokal yang akan diwariskan ke generasi yang akan datang. Kendati sudah diakui, perlindungan serta hak-hak masyarakat adat masih belum secara maksimal diterima oleh Masyarakat Adat Dayak Iban Sungai Utik. Hutan Adat Menua Sungai Utik masih saja terusik oleh pihak yang berwenang. Konflik semacam ini sering kali melibatkan ketidakselarasan antara perspektif masyarakat adat, pemerintah, dan pihak-pihak lain yang memiliki kepentingan dalam pengelolaan sumber daya alam terutama di Kawasan hutan adat Sungai Utik.Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian empiris dengan jenis pendekatan deskriptif analisis yaitu dengan menggunakan informasi, data dan fakta-fakta dilapangan yang akan dipergunakan untuk melakukan analisa permasalahan penelitian. Penelitian ini dilakukan melalui Teknik komunikasi langsung. Rumusan masalah penelitian ini adalah: Bagaimana Pengelolaan Kawasan Hutan Adat Pada Masyarakat Dayak Iban Sungai Utik Kapuas Hulu Pasca Diterbitkannya Surat Keputusan (SK) Penetapan Hutan Adat Dayak Iban Menua Sungai Utik. Adapun tujuan penelitian dari penelitian ini untuk mendapatkan data dan informasi, pengelolaan Kawasan hutan adat sebelum maupun pasca dikeluarkannya surat keputusan penetapan hutan adat , hambatan serta implikasi diterbitkannya Surat Keputusan (SK) Penetapan Hutan Adat terhadap tingkat konflik dan upaya masyarakat mencegah   koflik tenurial Berdasarkan hasil penelitian dapat diungkapkan bahwa pengelolaan kawasan hutan adat masyarakat Dayak Iban mengalami perubahan positif pasca dikeluarkannya Surat Keputusan (SK) penetapan hutan adat di Sungai Utik. Terdapat peningkatan kesadaran akan pentingnya menjaga kelestarian hutan adat, seiring dengan penerapan kebijakan yang lebih terstruktur dan terukur serta yang pastinya berkurangnya konflik tenurial yang terjadi dikawasan hutan adat d isungai utik.walaupun masih terdapat hambatan namun implikasi dikeluarkannya Surat Keputusan Penetapan Hutan Adat Sungai Utik mengalami penurunan tingkat konflik  Kata Kunci : Hutan Adat, Pengelolaan Hutan.